Sự tính toán obitan phân tử của phản ứng axit fulminic với phân tử hidro florua (HCNO+HF) - Nghĩa, Nguyễn Trọng; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2015)
A theoretical investigation of the HCNO + HF reaction, which is carried out by means of B3LYP/6-311G(d,p) + ZPVE computational method to determine a set of reasonable pathways. The potential energy surface for this system shows that there are nine different product pathways: PR1 (H2+FCNO), PR2 (FCN+H2O), PR3 (CH2F+NO), PR4 (HCNO_cy+HF), PR5 (HCN+HOF), PR6 (FCO+NH2), PR7 (OCNF+H2), PR8 (CO+NH2F) and PR9 (OCNH+HF). The results indicate that PR2 (FCN+H2O), PR9 (OCNH+HF) are the major product channels with minor contributions from PR8 (CO+NH2F) whereas the other channels for PR1 (H2+FCNO), PR3 (CH2F+NO), PR4 (HCNO_cy+HF), PR5 (HCN+HOF), PR6 (FCO+NH2), PR7 (OCNF+H2) are less favorable. Our study would be contributing to understand more about the reaction mechanisms of the HF with fulminic acid which is one of the important intermediates in the atmosphere and combustion chemistry.